Attitude towards recycling among business undergraduate students in Malaysia - Osman, Abdullah; Md Isa, Filzah; Othman, Siti Norezam; Jaganathan, Mathivannan (AENSI, 2014)
Pro-environmental concern is vital to each nation for continuous survival of future generations. Universities in Malaysia should inculcate pro-environmental behaviour among students since they are the future managers who will design and lead Malaysian organizations with better green strategies which will benefit both the organizations and the country.Objective of this study is probe the recycling behaviour among business undergraduate students in Malaysia. About 370 undergraduate business students from Universiti Malaya (UM), Universiti Putra Malaysia (UPM) and Universiti Utara Malaysia (UUM) participated in the study.The result indicates that the attitude of undergraduate business students on recycling is positive and able to influence their intention to perform recycling activities in their respective university campus. Intent to recycle depends on the sufficient knowledge and information they have whether it is been translated to their mind or behavioural belief.